“You Be The Judge”: An Analysis of the College Art Association’s Code of Best Practices in Fair Use for the Visual Arts - Lehrburger, Amy (The Columbia Journal of Law & the Arts, 2017)
This Note will aim to assess the workability of this Code of Best Practices, with a specific focus on the Principle and Limitations—which I call “Considerations”— set forward for Making Art. I will first look at the existing doctrine as it has developed over the last forty years, with specific attention to recent similarities and differences between decisions from the Second, Ninth, and Seventh Circuit Courts of Appeals. I will then turn to the CAA’s Code of Best Practices, contextualizing the project within the history of fair use statements and attempting to summarize relevant objections and defenses to such efforts. Finally, I will evaluate the Code, analyzing it as a descriptive and aspirational document, and presenting findings from interviews with artists applying the Code to Dieter’s hypothetical scenario. This Note argues that the Code of Best Practices is a problematic hybrid of descriptive and aspirational recommendations, instructive for artists only in terms of compliance with community norms, not with legal doctrine. Rather than offering recommendations for a better Code, I will suggest that none is needed for visual artists, in part because of their unique disposition as copyright users.